Prospective Preschool Teachers’ Metaphorical Perceptions about Art - Serhatlıoğlu, Birsen; İpek, Sinem (My University, 2019)
This study aims to determine prospective preschool teachers’ perceptions about the concept ofart through metaphors. The research was carried out in the phenomenological science pattern ofqualitative research methods. The research was carried out in the 2017-2018 school year withthe participation of 92 prospective preschool teachers who were registered in the Department ofPreschool Education in the Faculty of Education of a university located in the east of Türkiye.Participation in the study was voluntary based. For the selection of the sample, a simple randomsampling method was used. prospective preschool teachers were provided a form that is createdwith fill-in-the-gap sentences: “Art is like….. because……”. The collected forms were evaluated bythe content analysis method according to a qualitative research design. As a result of theanalysis, it was determined that prospective teachers produced 61 metaphors that werecollected under nine categories when the reasons for the metaphors were taken intoconsideration. Accordingly, the art of prospective preschool teachers; they come to theconclusion that they are perceived as a concept which requires originality and subjectivity,external expression, concretization, inspiration from nature, a basic necessity, peace and joy,beautiful and impressive, labor and care. Suggestions have been made under the light of theseresults.
Keywords: Eğitim; Eğitim Araştırmaları; Sanat